Faktor Risiko Ibu Untuk Terjadinya Partus Lama di RSUD Ulid Banjarmasin dan RSU Ratu Zalecha Martapura=Mother's risk factors toward the incidence of Prolonged labor at Ulin General Hospital in Banjarmasin and ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Abstract Maternal mortality-rate in Indonesia is still high, although government of Indonesia is making every efforts. Prolonged labor is contributed to maternal mortality rate and infant mortality rate. The study was conducted to identify risk factors associated with prolonged labor. It was a case-control study using 36 prolonged labor in Ulin General Hospital Banjarmasin and 39 prolonged labor in Ratu Zalecha General Hospital Martapura. Control group were normal labor in the same hospital and from the neighbourhood, 75 controls were in the same hospital and 75 controls were from neighbourhood. The data were collected through interview and direct observation in the field duringOctober 1st 2001 to September 30 th 2002. Risk factors studied were